Customer Satisfaction: Predicate of Service Quality and Price - Kuncoro, Amin (Global Health Science Group, 2023)
The aim of the research is to examine service quality and price on customer satisfaction for beauty products in Indonesia. The research design uses quantitative descriptive and quantitative grounded theory using primary data, namely respondents' answers through questionnaire statements and informants. The research sample was beauty product users in Indonesia, totaling 324 respondents spread across big cities and two informants. The research results explain that service quality can increase customer satisfaction and price can also improve customer quality. This proves that the respondents, most of whom are women from various circles, prefer to pay attention to their appearance by using beauty products that already have product names and clarity. However, an interesting finding from researchers is that some of the customers are men, better known as metrosexuals, namely men who pay attention to their appearance to support their work.